Accounting for the digital economy time for a fresh approach - Patricia Meredith (Centre for International Governance Innovation (CIGI), 2022)
Accounting standards that are used for tangible assets are not suitable for today's digital economy, which is fuelled by intangible assets. These standards need to reflect the shift in focus from tangible to intangible assets in order for the digital economy to thrive. Intangible assets such as design branding and software are not recognized by current accounting standards unless they are purchased from a third party. Without a shift in mindset that recognizes intangible assets and reflects the new economic reality, challenges will arise in making loans and investments and in taxing value creation. The accounting profession cannot act alone in making the shift and will need support from policy makers and regulators, investors, creditors and directors to make the necessary changes.
Keywords: 330